Penerapan Algoritma Pathfinding Pada Game Petualangan Pemadam Kebakaran Menggunakan Metode Learning Instructional Design - Kurniadi, Dede; Tresnawati, Dewi; Fitriani, Ranti (Jurnal Teknik Informatika dan Sistem Informasi, 2025)
Firefighters have responsibilities in fire and rescue incidents that do not exist in fire incidents, such as evacuating wasp nests, rescuing animals trapped in trees or wells, and so on. The importance of understanding the duties of a fire extinguisher is toprovide awareness to the public that with the existence of a fire extinguisher, the management of environmental resources is better maintained to realize environmental safety and security from the dangers of fire disasters. With very rapid technological information, presenting firefighting duties can be more interesting if presented with an adventure-themed 3D educational game. This research uses the Digital Game-Based Learning Instructional Design (DGBL-ID) method and applies a pathfinding algorithm to the path thatwill be taken. This research produces an Android-based firefighting adventure game application. Testing the level of user satisfactionobtained very satisfactory results, which were measured based on Black Box testing with the Guttman Scale method calculation.